2021
DOI: 10.1007/s10489-021-02645-3
|View full text |Cite
|
Sign up to set email alerts
|

Nation-wide human mobility prediction based on graph neural networks

Abstract: Nowadays, the anticipation of human mobility flow has important applications in many domains ranging from urban planning to epidemiology. Because of the high predictability of human movements, numerous successful solutions to perform such forecasting have been proposed. However, most focus on predicting human displacements on an intra-urban spatial scale. This study proposes a predictor for nation-wide mobility that allows anticipating inter-urban displacements at larger spatial granularity. For this goal, a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…In summary, this study revealed that geotagged Weibo data is representative of human mobility, which is consistent with recent research [43]. However, our research raises the issue of multi-dimensional heterogeneity which would be explored in the future with relevant learnings and other related models [44].…”
Section: Discussionsupporting
confidence: 91%
“…In summary, this study revealed that geotagged Weibo data is representative of human mobility, which is consistent with recent research [43]. However, our research raises the issue of multi-dimensional heterogeneity which would be explored in the future with relevant learnings and other related models [44].…”
Section: Discussionsupporting
confidence: 91%
“…With the development of information technology and statistics, many forecasting methods have emerged, and these mainly focus on econometrics, time series, Bayesian statistics, etc. In recent years, with the rapid development of artificial intelligence (AI) technology with big data and machine learning (ML) as the core, some scholars have tried to use ML technology for HMP [67][68][69][70][71][72][73]; however, the limitations include the limited amount of HM data, different standards, and difficulties in access. In addition, the uncertainty of HM drivers and the difficulty of their quantification have led to the slow development of HMP research [4].…”
Section: Of 19mentioning
confidence: 99%
“…While previous works [29,40,46,53] have used variations of DNNs to model mobility, they are limited due to the use of global information and do not handle significant link dynamics. While several works [1,17,37] leverage the generalization capability of Graph Neural Networks [5,24,39] for routing or network optimization they again do not handle link dynamics or device mobility.…”
Section: Dnns To Model Network Dynamicsmentioning
confidence: 99%